ASAS-ASAS QANUN PROVINSI ACEH NOMOR 6 TAHUN 2014 TENTANG HUKUM JINAYAT - achmad fikri oslami (Tazir, 2022)
ABSTRACT The principle of the formation of good laws and regulations is very necessary, so that regulations made in accordance with the direction and goals of the state are guided by legal development policies and do not become objects for material trials. The Aceh Qanun number 6 of 2014 concerning Jinayat Law also contains principles related to the formation of the Qanun. This research is a type of normative research, carried out using data obtained through legislation, Qanun, journals, books or online articles that still have the same connection and theme related to this research with primary data sources from Qanun number 6 of 2014 about Jinayat Law. The results of this study indicate that the Jinayat Law Qanun is based on Islam, Legality, Justice and Balance, Benefit, Protection of Human Rights and Learning to the Community (tadabbur). Where all the contents of the Qanun become an inseparable part of each other on the basis of the principles they have.. Keywords: Principles, Qanun, Jinayat Law